2011
DOI: 10.1371/journal.pone.0027863
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State EEG Source Localization and Functional Connectivity in Schizophrenia-Like Psychosis of Epilepsy

Abstract: BackgroundIt is unclear whether, like in schizophrenia, psychosis-related disruption in connectivity between certain regions, as an index of intrinsic functional disintegration, occurs in schizophrenia-like psychosis of epilepsy (SLPE). In this study, we sought to determine abnormal patterns of resting-state EEG oscillations and functional connectivity in patients with SLPE, compared with nonpsychotic epilepsy patients, and to assess correlations with psychopathological deficits.Methodology/Principal FindingsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(132 citation statements)
references
References 72 publications
3
128
0
1
Order By: Relevance
“…Both standardized LORETA and eLORETA showed the same low spatial resolution, with zero localization error in the presence of measurement and biological noise [60,62]. However, eLORETA exhibited a better source location in some control parameters [63].…”
Section: Cortical Sources Of Rseeg Epochs As Computed By Eloretamentioning
confidence: 99%
“…Both standardized LORETA and eLORETA showed the same low spatial resolution, with zero localization error in the presence of measurement and biological noise [60,62]. However, eLORETA exhibited a better source location in some control parameters [63].…”
Section: Cortical Sources Of Rseeg Epochs As Computed By Eloretamentioning
confidence: 99%
“…Lagged phase synchronization was used for measuring functional connectivity between the two BAs in the time period from stimulus onset to 300 msec poststimulus. Lagged phase synchronization measures the similarity (a corrected phase synchrony value) between signals in the frequency domain based on normalized (unit module) Fourier transforms; thus, it is related to nonlinear functional connectivity (Canuet et al, 2011). Lagged phase synchronization values are reported unit less in the range between 0 and 1.…”
Section: Eloreta Functional Connectivity Analysesmentioning
confidence: 99%
“…Further analyses were conducted by the eLORETA-KEY software package. We performed CSD analysis in the delta (2-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-60 Hz) frequency bands.…”
Section: Twentymentioning
confidence: 99%
“…22 Many studies have demonstrated the validity and reliability of the eLORETA method. 23 The aim of the present study was to determine whether specific EEG patterns in basal conditions and after CSF tapping are associated with the outcome of shunt operation in iNPH. We hypothesized that EEG changes after CSF tap test would be more related to shunt operation outcome than to brain activity before tapping.…”
Section: Introductionmentioning
confidence: 96%